Direct or Indirect Bandgap in Hybrid Lead Halide Perovskites?. Issue 10 (12th March 2018) - Sarritzu, Valerio; Sestu, Nicola; Marongiu, Daniela; Chang, Xueqing; Wang, Qingqian; Masi, Sofia; Colella, Silvia; Rizzo, Aurora; Gocalinska, Agnieszka; Pelucchi, Emanuele; Mercuri, Maria Laura; Quochi, Francesco; et al.
Abstract: Hybrid lead halide perovskites are unique solution‐processed semiconductors with very large optical absorption coefficients in the visible spectrum, large diffusion length of photoexcited charge carriers, and long excited state lifetimes, properties that have been exploited for the realization of solar cells and LEDs. However, one of the most fundamental properties of hybrid perovskites, whether the optical bandgap is direct or indirect, is actively debated. While perovskites have been considered direct bandgap semiconductors in most published literature, recent studies have proposed that the Rashba spin–orbit coupling gives rise to an indirect gap, few tens of meV lower in energy than the direct one. Here, the radiative recombination rates in hybrid perovskites are measured as a function of temperature, extracting their values from the instantaneous intensity of photoluminescence under pulsed excitation. Experimental data show that radiative recombination becomes faster with decreasing temperature, as in all direct bandgap materials and contrary to what expected for 3D Rashba semiconductors. The technique has been applied to CH3 NH3 PbI3 and CH3 NH3 PbBr3, both in polycrystalline and single crystal samples, as well as to GaAs for validation purposes. Abstract : Hybrid organic–inorganic lead halide perovskites are among the most studied solution‐process semiconductors, but it is not yet established whether their bandgap is direct, or if they are 3D Rashba semiconductors with an indirect gap. An experiment here distinguishes the two scenarios by measuring the radiative recombination rate as a function of temperature and identifies hybrid perovskites as direct gap semiconductors.